Kontribusi Kepemimpinan Situasional Kepala Sekolah, Upaya Meningkatkan Iklim Kerja Guru - Suhaili Munahar (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2019)
This study aims to determine and analyze the contribution of situational leadership to school principals in an effort to improve the work climate of teachers. The subject population included 50 teachers from SMP Negeri 2 Sikur. This study uses a census study, with ex-post facto design. Data were analyzed by multiple regression and correlation analysis. The results showed that there was a positive and significant contribution between the principal's situational leadership in improving the teacher's work climate with a contribution of 62.5%. Therefore the principal's situational leadership on the work climate functions as a predictor of teacher performance in SMP Negeri 2 Sikur, East Lombok Regency.